A longitudinal study on change in empathy in the first two years among medical students - Arjyal, Amit; GC, Krishna Bahadur; Subedi, Madhusudan; Gongal, Rajesh Nath (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Change of empathy as students progress through medical school has been varyingly described with some studies reporting a decline and others little change. This study longitudinally assessed empathy change from the start of the first year to the start of the third year in a batch of medical students.Method: This study was carried out at Patan Academy of Health Sciences which has adopted an innovative basic sciences curriculum comprised of medical humanities, problem based learning, rural residential postings, early patient interactions and longitudinal chronic patient follow-ups. Students in the intake of 2019-20 filled the Jefferson Scale of Empathy-Student version questionnaire at the start of first and third years. Participants provided voluntary informed consent. Institutional Review Committee granted ethical approval to the research.Result: Fifty-three students who participated in the study at the start of the first year were followed up at the start of the third year. The mean(±SD) empathy score showed a significant rise at the start of the third year, 112.9(±8.7) compared to the score at the start of the first year 105.6(±10.5) with a rise of 7.2 points (95% CI=3.8-10.7), p-value